New Understanding of Transient Pressure Response in the Transition Zone of Oil-Water and Gas-Water Systems - Wenbin Xu; Zhihui Liu; Jie Liu; Yongfei Yang (Geofluids)
Well test analysis requires a preselected model, which relies on the context input and the diagnostic result through the pressure logarithmic derivative curve. Transient pressure outer boundary response heavily impacts on the selection of such a model. Traditional boundary-type curves used for such diagnostic purpose are only suitable for single-phase flow in a homogeneous reservoir, while practical situations are often much more complicated. This is particularly true when transient pressure is derived during the field development phase, for example, from permanent down-hole gauge (PDG), where outer boundary condition such as an active aquifer with a transition zone above it plays a big role in dominating the late time pressure response. In this case, capillary pressure and the total mobility in the transition zone have significant effect on the pressure response. This effect is distinctly different for oil-water system and gas water system, which will result in the pressure logarithmic derivatives remarkably different from the traditional boundary-type curves. This paper presents study results derived through theoretical and numerical well testing approaches to solve this problem. The outcome of this study can help in understanding the reservoir behavior and guiding the management of mature field. According to the theoretical development by Thompson, a new approach was derived according to Darcy’s law, which shows that pressure response in the transition zone is a function of total effective mobility. For oil-water system, the total effective mobility increases with an increase in the radius of transition zone, while for gas-water system, the effect is opposite.